Розробка методу автоматичного оцінювання відповідей студентів з використанням GPT-моделей від OpenAI для веб-застосунку з тестування знань мови SQL - Науменко, В. В. (ХНУРЕ, 2024)
This paper is devoted to the development of a method for automatically evaluating students’ answers using OpenAI GPT models for a web application designed to test SQL knowledge to replace the previous heuristic approach. The method uses the capabilities of GPT models to analyze a teacter’s SQL script and a student’s script, which allows to automatically evaluate students’ answers when taking SQL tests. Thanks to this approach, the web application provides more efficient and automated testing, which will help bring the automatic system of evaluating students’ answers closer to the level of evaluation by a real teacher
Keywords: автоматичне оцінювання відповідей студентів; GPT-модель